Top determinants of corporate reputation management - Nirvana Bechan (Communicare)
Positive reputation is a valuable corporate asset and needs to be managed proactively in response to new threats entering the marketplace. Recent events have shown that the reputation of an organisation can take years to build, yet takes only a few seconds to destroy. In this study, it is suggested that knowing the top determinants of current reputation management can only help to enhance the business objectives of an organisation by contributing to the bottom line and gaining a competitive advantage. This paper looks at what communication managers in toplisted companies operating in South African consider the top determinants of managing corporate reputation in their organisations to be. The paper draws links between managing organisational reputation and stakeholder management, and provides valuable findings for communication specialists working in positions of management.